1999
DOI: 10.1038/sj.gt.3300839
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirally transduced bone marrow stromal cells isolated from a mouse model of human osteogenesis imperfecta (oim) persist in bone and retain the ability to form cartilage and bone after extended passaging

Abstract: Bone marrow stromal cells isolated from a model of osteoon the edges of the trabecular bone of the injected and genesis imperfecta (oim) mice, were transduced with a contralateral femurs by X-gal staining and PCR analysis at retrovirus (BAG) carrying the LacZ and neo r genes after 4, 10, 20, 30 and 40 days after injection. The LacZ gene passage 21. The transduced cells retained the ability to was also detected in the lung and liver of the recipient mice express alkaline phosphatase activity in vitro when treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 35 publications
(39 reference statements)
3
36
0
1
Order By: Relevance
“…These tissues have been demonstrated to contain stem cells of mesenchymal origin, which have potential to differentiate into various specific tissue cell phenotypes that include tendon, fat, marrow stroma, dermis, muscle, bone, and cartilage [10,[12][13][14][15][16][17][18][19][20]. Numerous studies have demonstrated that bone marrow-derived mesenchymal stem cells (MSCs) can give rise to chondrocytes under appropriate conditions [21][22][23]. Members of the TGF-β1 (transforming growth factor 1) super-family have been shown to play a role in the induction of chondrogenic differentiation of MSCs in vitro [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These tissues have been demonstrated to contain stem cells of mesenchymal origin, which have potential to differentiate into various specific tissue cell phenotypes that include tendon, fat, marrow stroma, dermis, muscle, bone, and cartilage [10,[12][13][14][15][16][17][18][19][20]. Numerous studies have demonstrated that bone marrow-derived mesenchymal stem cells (MSCs) can give rise to chondrocytes under appropriate conditions [21][22][23]. Members of the TGF-β1 (transforming growth factor 1) super-family have been shown to play a role in the induction of chondrogenic differentiation of MSCs in vitro [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…38 Several other investigators have reported similar findings in murine, sheep and baboon animal models. [39][40][41][42] Using similar approaches as above but with bettercharacterized mouse bone marrow stromal cells, the current authors have shown that cells infused into mouse femurs persist in bone. Murine adherent marrow stromal cells were established using standard methods and were then marked by transduction with a retrovirus carrying the LacZ marker gene.…”
Section: Cell Therapymentioning
confidence: 88%
“…39,43 Infusion of the cells into immunecompetent mice demonstrated that the cells colonized the bones of the recipient mice and differentiated into osteoblasts in vivo. 39,43 Prompted by the murine studies, human clinical trials in children with severe OI were initiated by Horwitz and colleagues using whole marrow harvested from leukocyte antigen (HLA) matched donors. Five children were enrolled in the trial and subjected to irradiation followed by bone marrow transplantation from matched donors.…”
Section: Analysis Of the Ceramic Cubes At Different Time Pointsmentioning
confidence: 99%
See 2 more Smart Citations